MEMBANGUN SISTEM INFORMASI WEBSITE DENGAN PENERAPAN METODE WATERFALL (STUDI KASUS : SMA XAVERIUS 5 BELITANG ) - Wisnumurti Wisnumurti; Sri Hartati (Universitas Mahakarya Asia, 2018)
By utilizing computer-based information technology with internet facilities, SMA Xaverius 5 Belitang builds an Information System that provides information about SMA Xaverius 5 Belitang. The purpose of this study is to build a website information system with the application of the Waterfall Method at SMA Xaverius 5 Belitang. The method used in the information system of SMA Xaverius 5 Belitang, as well as to find out which system is running, uses a structured approach using several tools such as Uml, use case diagrams, activity diagrams, sequence diagrams, class diagrams, while for the system development method using linear sequential or often referred to as the